(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article outlines ways of developing the competence of positively resolving conflict situations in future teachers. It highlights the complex nature of conflicts, showing that they contain both destructive and constructive aspects, as well as elements of violence and cooperation. At the same time, the article подробно explains approaches aimed at resolving conflicts and fostering mutual understanding between the parties involved.